Novel terephthalamide diol monomers synthesis from PET waste to Poly(Urethane acrylates) - Pastore, Genny; Giacomantonio, Roberto; Lupidi, Gabriele; Stella, Francesca; Risoluti, Roberta; Papa, Elena; Ballini, Roberto; Sarasini, Fabrizio; Tirillò, Jacopo; Marcantoni, Enrico; Gabrielli, Serena (Frontiers in Chemistry, 2023)
Due to its excellent properties, poly(ethylene terephthalate) (PET) is one of the most produced and consumed polymers. Among plastics, it represents the main contributor to environmental pollution. Following the circular economy model, the chemical upcycling of PET reduces the amount of waste generated and transforms it into high-value products. The depolymerization of poly(ethylene terephthalate) into oligomers or monomers leads to forming a library of reactive molecules involved in different polymerization processes to obtain compounds with improved properties. Herein, several β-hydroxy amines were synthesized and used for the chemical recycling of water bottle waste by an environmental benefit aminolysis process to get very useful new terephthalamide diol monomers. The recycled diol monomers were subsequently exploited to synthesize poly(urethane acrylates) (PUAs) UV-curable coatings, and their chemical, thermal and mechanical characterizations were performed. The results show the great potential of the developed synthesis protocols to obtain PUAs with final properties that can be modulated to meet the requirements of different applications.